Alleviating Poverty and Achieving Inclusive Growth Through Msmes’ Digital Innovation - Hasan Hasan; Windi Novia Ratri Wardhani; Ratih Pratiwi; Melyn Eta Coriala; Luluk Mubarokah (AKUNTABILITAS, 2023)
Inequality and poverty are interrelated factors with negative influences on economic growth. Inequality can undermine institutional efficiency that propagates economic security. Poverty will have different influences along with the effects of inequality on the society. Poverty negatively influences consumption growth and, consequently, decreases as the economy grows. Technology is a strategy to deal with ongoing developments in the era of globalization and digitalization characterized with mobility of goods and services, capital flows, and use of technology. MSMEs’ development through technological innovations developing in the community is expected to expand market coverage and accelerate the structural transformation process. Alleviating poverty and achieving inclusive growth through MSMEs’ digital innovation of SMEs are recommended to be carried out through 4 (four) policy pillars: strengthening MSMEs’ digital literacy; increasing SMEs’ skills and capabilities; legal licensing; and MSMEs’ financial literacy and accessibility